Prevalence of somatic and urogenital symptoms as well as psychological health in women aged 45 to 55 attending primary health care: a cross-sectional study - Lena Rindner; Gunilla Strömme; Lena Nordeman; Margareta Wigren; Dominique Hange; Ronny Gunnarsson; Gun Rembeck (BMC, 2017)
Abstract Background Women's physical and mental ill-health such as stress-related symptoms, depression, pain, hypertension and urogenital health shows a marked increase around the ages 45-55 years. These women are an important group for Primary Health Care (PHC) due to their prevalent symptoms and illnesses. The aim of this study was to estimate the prevalence of somatic, psychological and urogenital symptoms in women aged 45-55 attending PHC and evaluate factors associated with severe symptoms. Methods One hundred and thirty-one women were recruited from PHC in southwestern Sweden. Data were obtained from two self-reported questionnaires, the Menopause Rating Scale (MRS) and the Montgomery-Asberg Depression Rating Scale (MADRS). Results Exhaustion, depressive mood, muscle and joint problems, sleep and sexual problems were the most prevalent reported symptoms. Half of the women reported heart discomfort. Depression and increasing age were correlated to more severe symptoms. Conclusion We recommend that cardiovascular risk factors, musculoskeletal symptoms, sexual problems, sleeping problems and mental health should be actively asked for when women aged 45 to 55 attend PHC. We propose that preventive counselling of women in PHC before the age 45 should be evaluated in future studies.